Promoting an Eco-ELT Based Learning Model for Semantics in English Education - Misbah, Hasanul (International Journal on Advanced Science, Education, and Religion, 2024)
This article discusses the promotion of an Eco-ELT-based learning model in the teaching of semantics in English education. Building on the concept of Eco-ELT (Ecological English Language Teaching) proposed by Saiful (2023), this paper outlines how semantics can be effectively integrated into this innovative model. The article explores relevant semantics learning materials, potential teaching methods, and assessment strategies, all framed within the context of an ecological approach that emphasizes sustainability, community, and environmental awareness. The Eco-ELT model is envisioned as a means to foster holistic and contextual language learning, while also addressing global challenges and promoting critical thinking.